THE INTERPRETATION OF INCOME IN A PERIOD OF INFLATED PRICES. - Niswonger, C. R. (The Accounting Review, 1949)
Abstract The primary problem in the determination and interpretation of income during a period of rapidly increasing prices is caused by the matching of revenues at current price levels with costs which represent the expiration of assets acquired at materially lower price levels. Expenses or costs chargeable against revenue during an accounting period may be divided into two categories: those which arise from a current disbursement of cash or the incurrence of a liability, and those which represent the using up of assets which were acquired in a previous period. When the benefits derived from a particular item of expense, such as sales salaries, are deemed to be realized at about the same time the expenditure is incurred, the purchasing power of the dollars of revenue and of the dollars of expense may, for practical purposes, be considered to be the same. When, however, the benefits derived from the consumption of an asset acquired in a previous period are matched against revenues of the current year the dollars of revenue and of expense which are being compared do not have the same values.